Concise Review: Evidence for CD34 as a Common Marker for Diverse Progenitors. (June 2014) - Sidney, Laura E.; Branch, Matthew J.; Dunphy, Siobhán E.; Dua, Harminder S.; Hopkinson, Andrew
Abstract: CD34 is a transmembrane phosphoglycoprotein, first identified on hematopoietic stem and progenitor cells. Clinically, it is associated with the selection and enrichment of hematopoietic stem cells for bone marrow transplants. Due to these historical and clinical associations, CD34 expression is almost ubiquitously related to hematopoietic cells, and it is a common misconception that CD34‐positive (CD34 + ) cells in nonhematopoietic samples represent hematopoietic contamination. The prevailing school of thought states that multipotent mesenchymal stromal cells (MSC) do not express CD34. However, strong evidence demonstrates CD34 is expressed not only by MSC but by a multitude of other nonhematopoietic cell types including muscle satellite cells, corneal keratocytes, interstitial cells, epithelial progenitors, and vascular endothelial progenitors. In many cases, the CD34 + cells represent a small proportion of the total cell population and also indicate a distinct subset of cells with enhanced progenitor activity. Herein, we explore common traits between cells that express CD34, including associated markers, morphology and differentiation potential. We endeavor to highlight key similarities between CD34 + cells, with a focus on progenitor activity. A common function of CD34 has yet to be elucidated, but by analyzing and understanding links between CD34 + cells, we hope to be able to offer an insight into the overlapping properties of cells that express CD34. Stem Cells 2014;32:1380–1389